Vacuum frequency measurement of 7S3-7P4 transition in Cr atoms using laser-induced fluorescence - Tong Zhou; Xiao Deng; Zhijun Yin; Guangxu Xiao; Junyu Shen; Lei Sun; Fangsheng Ren; Dongbai Xue; Yuying Xie; Jing Yu; Ming Kong; Jianbo Wang; et al. (Applied Physics Express)
The nanometric length traceability chain is the foundation of cutting-edge research at the nanoscale. The current traceability chain has limitations in its applications. However, the application performance of the nanometric traceability chain based on the ^7 S _3 - ^7 P _4 transition in chromium atoms has been fully validated. Addressing the issue that the ^7 S _3 - ^7 P _4 transition frequency at the traceability side of this chain has not been measured in a vacuum environment, this study used the fluorescence symmetry method under vacuum conditions to measure the ^7 S _3 - ^7 P _4 transition frequency, obtaining the corresponding vacuum wavelength of 425.5533474 nm and the vacuum wave number of 23498.81645 cm ^−1 .